Pengaruh Padi Lokal Jambi dan Padi Unggul Nasional terhadap Pengaplikasian Biochar di Lahan Rawa Pasang Surut - Dody Perwira; Aryunis Aryunis; Ahmad Riduan (Jurnal Ilmiah Universitas Batanghari Jambi, 2023)
This study aims to provide information on the effective and efficient provision of rice husk biochar and betel nut biochar for the growth and production of rice crops in tidal marshlands. The research was carried out in community rice fields located in Pembengis Village, Bram Itam District, Tanjung Jabung Barat Regency, Jambi Province with a height of 3 meters above sea level (masl). This study used a Randomized Group Design (RAK) with two factors, the first treatment factor is the rice plant variety consisting of local varieties of white works, high strong local varieties, high-yielding varieties of inpara 3 and superior varieties of inpari 32, the second treatment factor is biochar consisting of no biochar as a control, rice husk biochar and betel nut coir biochar. Each treatment is repeated 3 times. The variables observed were plant height, maximum number of saplings per clump, number of productive saplings, panicle length, amount of grain per panicle, percentage of hollowness per panicle, yield of milled dry grain, weight of 100 grains of grain, length of roots and amount of grain contents per panicle. The results showed that the application of biochar to superior and local rice plants had a significant influence on several variables. There was an interaction between high-yielding varieties and local varieties with the application of rice husk biochar and betel nut coir biochar in tidal marshlands.